Déjà vu all over again: racial, ethnic and age disparities in mortality from influenza 1918–19 and COVID-19 in the United States. Issue 4 (April 2022) - Koziol, James A.; Schnitzer, Jan E.
Abstract: Background: Examination of the mortality patterns in the United States among racial, ethnic, and age groups attributed to the 1918–19 influenza pandemic revealed stark disparities, causes for which could have been addressed and rectified this past century. However, these disparities have been amplified during the current COVID-19 pandemic. We have ignored the lessons of the past, and were destined to repeat its failings. Objectives: Compare and contrast mortality patterns by age, race, and ethnicity attributable to the 1918–19 influenza pandemic in the United States with corresponding patterns during the COVID-19 pandemic. Methods: This is a retrospective study, establishing mortality rates according to age, race and ethnicity attributable to the 1918–19 influenza pandemic in the United States and to the current COVID-19 pandemic, using mortality data published by the U.S. Public Health Service and the Centers for Disease Control and Prevention. Negative binomial regression models were used to establish rate ratios, that is, ratios of mortality rates across the various racial/ethnic groups, and associated 95% confidence intervals. Results: Mortality patterns by age differ significantly between the 1918–19 influenza pandemic and the COVID-19 pandemic: with infant and young adult (25–40 years old) mortality substantially higher in the former. Disparities in mortality between racial and ethnic groups are amplified in the COVID-19 pandemic compared to the 1918–19 experience. Conclusions: As we evaluate our nation's response to COVID-19 and design public policy to prepare better for coming pandemics, we cannot ignore the stark disparities in mortality rates experienced by different racial and ethnic groups. This will require a sustained resolve by society and government to delineate and remedy the causative factors, through science devoid of political interpretation and exploitation. Abstract : Public health; 1918 Influenza pandemic; COVID-19 pandemic.